Efeitos da Angiotensina-(1-7) na inflamação e reparo tecidual - Deconte, Simone Ramos (2014)
Background: (Ang-(1-7)), a bioactive heptapeptide formed from the fragmentation of angiotensin I and acts as an antagonist of angiotensin II and carries anti angiogenic, antifibrotic, antiproliferative properties. However, the effects of this peptide on the development of fibroproliferative tissue induced by synthetic sponge matrix has not been fully characterized. Methods: Male Swiss mice (7-8 weeks) were implanted subcutaneously with polyether-polyurethane sponge discs for induction of the fibrovascular tissue. Ang-(1-7) treatment (30ng) was carried out by intraimplant daily administration. Implants collected 1, 4, 7, 9 and 14 days postimplantation were analyzed for determination of angiogenesis (hemoglobin (Hb), blood vessels number and levels of pro-angiogenic cytokines (VEGF and bFGF), inflammation (myeloperoxidase- MPO and N-acetyl-P-D-glucosaminidase-NAG activities and levels of pro-inflammatory cytokines -TNF-a, CXCL1/KC and CCL2) and fibrogenesis (collagen deposition and TGFP-1 levels). Results: Ang-(1-7) exerted dual effects of the development of neovascularization in the sponge implants as assessed by measuring Hb content and number of vessels. At days 4 and 7 the peptide inhibited increases of these parameters when compared with the non-treated group. From day 9 onwards, the peptide increased hemoglobin (42%), vessel number (46%), FGF (24%) and VEGF level (29%) relative to the control group. This pattern was also observed for the inflammatory marker and cytokine production. The Ang-(1-7) treatment was able to decreased CXCL1 (48%), TNF-a (25%), NAG (58%), CCL2 (32%) from day 1 and MPO (27%) from day 3 relative to the control group. This pattern changed relative to tissue repair in sponge implants. Total soluble collagen (105%), collagen content (37%) and TGF-P1(50%) were increased after 7 days of treatment with Ang-(1-7). During these 14 days there was involvement of processes of fibrosis and tissue remodeling, as shown by mast cells number that were greater than control group (32%)(p<0.05).Conclusion: After 14 days of treatment the inhibitory effect of Ang-(1-7) to attenuate inflammation and promote angiogenesis and fibrogenic components of the fibrovascular tissue induced by the synthetic matrix extends the range of actions of the Ang-(1-7) and may indicate its therapeutic potential in controlling diseases.